THE INFLUENCE OF DIVIDEND POLICY, FIRM SIZE, CAPITAL STRUCTURE, AND CSR ON BANKING COMPANIES’ VALUE - Wijaya, Henryanto; Andy, Andy; Febrianty, Levina; Morgan, Christopher Elihu Billy (Graduate Program of Universitas Tarumanagara, 2023)
The research examined the effect of dividend policy, firm size, capital structure, and Corporate Social Responsibility (CSR) on firm value in Indonesian banking companies listed on the Indonesian Stock Exchange (IDX). Purposive sampling was used to select the sample, and the population for this study was from 2017 to 2020, with 48 data points representing 12 samples of banking companies. According to the findings of this study, firm size and corporate social responsibility (CSR) both have a positive and significant effect on firm value. The dividend policies and capital structure have a small but positive impact on firm value. The descriptive research design was used in this study. This descriptive research aimed to ascertain the existence of one or more variables without comparing them directly and instead of looking for relationships with other variables. The data processing in this study was performed using the Microsoft Excel 2010 program, and the data analysis was performed using Eviews version 11. This study employed a technique known as purposive sampling to select random samples.